Performance Assessment of Ultra-High Durability Concrete Produced From Recycled Ultra-High Durability Concrete - Borg, Ruben Paul; Cuenca, Estefania; Garofalo, Roberto; Schillani, Fabrizio; Nasner, Milena Lozano; Ferrara, Liberato (Frontiers in Built Environment, 2021)
The purpose of the work reported in this paper is to assess the performance of Recycled Ultra High Durability Concrete (R-UHDC), produced using different fractions of recycled aggregate obtained from crushed Ultra High Durability Concrete (UHDC), as a substitute of the natural aggregate. Four different Recycled Ultra High Durability Concrete mixes (R-UHDC) were designed and manufactured with a reference mix based on natural aggregate and three mixes with the natural aggregate replaced using recycled UHDC according to two percentage replacement values (50% and 100%). The effect of environmental degradation of the recycled parent concrete was also addressed, using recycled aggregates subjected to accelerated carbonation (replacement percentage equal to 50%) The work has been conducted in the framework of the activities of the Horizon 2020 ReSHEALience Project in Ultra High Durability Concrete. One key objective of the project was to formulate the concept and experimentally validate the performance of Ultra High Durability Concrete for structures and infrastructures exposed to extremely aggressive scenarios. The ReSHEALience consortium has defined UHDC as a “strain-hardening (fibre reinforced) cementitious material with functionalizing micro- and nano-scale constituents especially added to deliver high durability in the cracked state under extremely aggressive exposure conditions”. In this context, the research was conducted to investigate the potential of recycling the produced and validated UHDCs, and employing them as a partial or even total replacement of natural sand in the production of a new UHDC. This supports the cradle-to-cradle approach in life cycle engineering applications. The research confirmed the effective regeneration of new UHDC based on recycled aggregate obtained from crushed UHDC, attaining the required rheological characteristics, mechanical properties (compressive, flexural strength and toughness) and durability performance (chloride penetration resistance, chloride migration, water capillary suction and resistivity). This work is intended as the first step towards the sustainability assessment of the end of life of UHDC materials and structures and the potential of recycled-UHDC for new and retrofitting structural applications.